New instrumentation at the centre for harbour and coastal studies of Cedex:Examples and applications (2020)
The Centre for Harbour and Coastal Studies of CEDEX (Spain) is continuously carrying out physical model experimental studies in its Experimental Maritime Laboratory, both for applied research and consultancy in the maritime hydraulics field. These activities, especially the applied research, allow introducing and developing of new types of instrumentation. The obtained results are used to gain not only a better knowledge of different types of flows and their interaction with maritime structures, but constitute a valuable data base for numerical model calibration and validation.